Supplementation of inorganic and organic zinc mixtures in feed of Boerka goats fed by oil palm fronds - Simon P. Ginting; Antonius .; Kiston Simanihuruk (Jurnal Ilmu Ternak dan Veteriner, 2017)
Zinc is an element of many enzymes and hormones having very important physiological functions in the body so that it influences the production and reproduction of animals including the activity of the rumen microflora in degrading fiber in a diet. The aim of this study was to improve the performances of goats offered oil palm fronds based diets through the supplementation of 35 ppm of Zn in the form of inorganic (ZnO) and organic zinc (Zn-methionine). Thirty mature male crossing Boer x Kacang (Boerka) goats were divided into five groups and randomly allocated to one of the five feed treatments as follows: P1: complete feed based on the palm oil fronds (Control), P2: P1 + 35 ppm Zn (100% Zn0), P3: P1 + 35 ppm Zn (75% Zn0 + 25% Zn-methionine), P4: P1 + 35 ppm Zn (50% Zn0 + 50% Zn-methionine), P5: P1 + 35 ppm Zn (25% Zn0 + 75% Zn-methionine). The experiment was conducted in a Completely Randomized Design of six replications. Increasing the proportion of Zn methionine in the mixtures elevated feed consumption, and the highest feed intake was observed in goats received 75% Zn-methionine/25% ZnO. Daily body weight gains was only affected (P<0.05) by the 75% Zn-methionine/25% ZnO supplement. The concentration of Zn in the blood increased significantly (P<0.05) when Zn methionine was added and it increased steadily as the proportion of Zn methionine greater in the mixtures, but the VFA compositions of the rumen were not affected (P>0.05) by Zn supplementation. It is concluded that the performances of goat fed complete diets based on the oil palm fronds could be improved by supplementation of inorganic and organic Zn mixture.